Life Cycle Assessment Analysis of the Environment Load from Typical Chinese Steel Enterprises - Na, Hongming; Gao, Chengkang; Zhang, Menghui; Qi, Zhaoqian; Ye, Zhou (Journal of Environmental Accounting and Management, 2026)
The environmental load of different steelmaking processes at two typical steel production facilities in Jiu Steel was analyzed and evaluated by Life Cycle Assessment. The environment impacts of different steelmaking processes were classified by Environmental impact classification methods offered by the GaBi software, with the addition of characteristic factors; The environment impacts of producing 1 ton steel was quantified. Results shows that the major environmental impacts of Basic Oxygen Furnace steelmaking process are toxicity to aquatic ecosystems, toxicity to humans, depletion of fossil energy, and depletion of mineral resources, with these resulting from processes of coking, sintering, blast furnace iron-making, and waste iron recycling. Climate change, toxicity to humans, toxicity to aquatic ecosystems, and solid waste production make up 30%, 95%, 50%, and 90% respectively of the total environmental impact. The major environmental impacts of Electric Arc Furnace steelmaking process are climate change, acidification, and photochemical ozone formation from molten iron and electric steelmaking processes. A reliable theoretical basis for steelmakers to adjust the two different processes is provided through this work. The research may also contribute to detecting potential for improvement, including for energy saving and for reducing the environmental load of various aspects of the production process. Steelmakers can therefore improve and optimise their production processes.